2003
DOI: 10.1677/joe.0.1760267
|View full text |Cite
|
Sign up to set email alerts
|

The phytoestrogen genistein suppresses cell-mediated immunity in mice

Abstract: The soy phytoestrogen, genistein, induces thymic atrophy when administered to ovariectomized mice by injection or in the diet. Injected genistein also causes decreased humoral immunity, but the effects of genistein on cellmediated immunity have not been addressed. Here we examined effects of injected and dietary genistein on cell-mediated immune responses. Female C57BL/6 mice (25-to 27-days-old) were ovariectomized, then placed on phytoestrogen-free feed 5 days later. Seven days after ovariectomy, they were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 37 publications
3
57
1
2
Order By: Relevance
“…Injection of genistein into ovariectomized adult mice at a concentration that produced similar serum genistein levels to those reported in soy-fed human infants resulted in significant loss of weight of the thymus gland, apoptosis of thymocytes leading to drastically reduced thymocyte numbers, changes in spleen cell numbers, and reduced humoral immunity (199). In a subsequent study, the same treatment reduced cellular immunity (200). In both studies, the effects of genistein were concluded to occur through ER-dependent and independent pathways.…”
Section: Inflammation and Immunitymentioning
confidence: 62%
“…Injection of genistein into ovariectomized adult mice at a concentration that produced similar serum genistein levels to those reported in soy-fed human infants resulted in significant loss of weight of the thymus gland, apoptosis of thymocytes leading to drastically reduced thymocyte numbers, changes in spleen cell numbers, and reduced humoral immunity (199). In a subsequent study, the same treatment reduced cellular immunity (200). In both studies, the effects of genistein were concluded to occur through ER-dependent and independent pathways.…”
Section: Inflammation and Immunitymentioning
confidence: 62%
“…Isoflavones were shown to affect chemotactic factors production (60-62), oxygen radical generation (63)(64)(65)(66), adhesion molecule expression (67-69) and alter arachidonic acid metabolism (70)(71)(72), compatible with their anti-inflammatory effects. Dietary and injected genistein suppressed cell-mediated immunity in mice even at levels similar to those obtained in human diet (73). As cell activity recovered to normal after the treatment was stopped, it has been suggested that immune changes caused by genistein may be reversible.…”
Section: Phytoestrogens Gender and Allergic Responsementioning
confidence: 87%
“…Delayed -type hypersensitivity (DTH) reaction is classified as type IV allergy response and is mainly mediated by T cells and macrophages. Genistein suppresses DTH reaction to oxazolone and granulocyte -mediated response (15). In addition to cellular immune response, genistein also suppresses antigen (Ag) -induced antibody (Ab) production.…”
Section: ) Cellular and Humoral Immune Responsesmentioning
confidence: 99%